Interplay of plasma Oxytocin and oxytocin receptor gene methylation levels on empathy in older adults - Rebecca J. Polk; Kylie A. Wright; Tian Lin; Kathleen Krol; Allison M. Perkeybile; Hans P. Nazarloo; C. Sue Carter; Jessica Connelly; Natalie C. Ebner (Scientific Reports)
Abstract Oxytocin (OT) levels in blood plasma and OT receptor gene (OXTRm) methylation are two crucial pieces of the endogenous OT system that have been independently associated with social cognition. Empathy is a social-cognitive skill essential for understanding others’ emotions and intentions, making it vital for everyday social interactions across the lifespan. Associations of plasma OT and OXTRm levels with empathy are currently not well understood among older adults, despite this period being marked by changes in both the endogenous OT system and empathy. Tying these previously separate lines of research together, this study examined the interplay of plasma OT and OXTRm on empathy in generally healthy older adults. Plasma OT levels were not directly related to empathy but for older adults with higher OXTRm levels higher plasma OT levels were associated with lower empathy scores. These results contribute to a growing literature on the intricate role of the endogenous OT system in social cognition in aging.